2009
DOI: 10.1111/j.1750-3841.2009.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Washing Treatments and Alkali Extraction on Gelation Characteristics of Striped Catfish (Pangasius hypophthalmus) Muscle Protein

Abstract: The effect of washing treatments (water and alkali washing) and alkali extraction/acid precipitation on the physicochemical and textural properties of striped catfish (Pangasius hypophthalmus) muscle protein was compared. Alkali extraction/acid precipitation process resulted in the highest protein recovery of 98.77% (dry weight basis) and lowest fat content of 0.98% (dry weight basis). The extractable proteins of fish protein isolates (FPI) at various ionic strengths (0 to 0.6 M NaCl) exhibited majority of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 42 publications
3
21
3
Order By: Relevance
“…These interactions may lead to formation of a gel network with increased hardness. Tadpitchayangkoon and Yongsawatdigul (2009) hypothesized that such a gel network would differ from a typical gel network of myofibrillar proteins. Elastic gels are derived from numerous crosslinks between the myofibrillar proteins.…”
Section: Resultsmentioning
confidence: 98%
“…These interactions may lead to formation of a gel network with increased hardness. Tadpitchayangkoon and Yongsawatdigul (2009) hypothesized that such a gel network would differ from a typical gel network of myofibrillar proteins. Elastic gels are derived from numerous crosslinks between the myofibrillar proteins.…”
Section: Resultsmentioning
confidence: 98%
“…Breaking force ( g ) and deformation (mm), which were used as indexes of fracturability (brittleness) and cohesiveness, respectively, were determined according to Tadpitchayangkoon and Yongsawatdigul (2009) by TA.XT Plus texture analyzer (Stable Micro System, Godalming, Surry, UK). After equilibrium at room temperature for 2 h, gels were cut into pieces of 25 mm in height and 30 cm in diameter.…”
Section: Methodsmentioning
confidence: 99%
“…The positive results of three-washing cycles have been widely reported in various species including striped catfish (Pangasius hypophthalmus) (Tadpitchayangkoon and Yongsawatdigul, 2009). However, Jin et al (2007) demonstrated that two-washing cycles of Alaska pollock mince resulted in a relatively high breaking force and deformation due to the residual transglutaminase (TGase) activity in the cytosolic fraction.…”
Section: Introductionmentioning
confidence: 98%